2000
DOI: 10.1002/1097-0061(20000315)16:4<365::aid-yea526>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and phenotypic analysis of six open reading frames from the left arm ofSaccharomyces cerevisiae chromosome VII

Abstract: Six open reading frames (ORFs) from Saccharomyces cerevisiae chromosome VII were deleted using the kanMX4 module and the long‐flanking homology‐PCR replacement strategy in at least two different backgrounds. Among these ORFs, two of them (YGL100w and YGL094c) are now known genes which encode well‐characterized proteins (Seh1p, a nuclear pore protein, and Pan2p, a component of Pab1p‐stimulated poly(A) ribonuclease, respectively). The other four ORFs (YGL101w, YGL099w, YGL098w and YGL096w) code for proteins of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It encodes a protein carrying a potential ATP/GTP binding motif that has numerous homologues in databases. The null mutant displayed slow growth and abnormal morphology (Lillo et al, 2000). Our data suggest that modifications in the wall of these cells may arise from impaired glycosylation.…”
Section: Deletions That Directly or Indirectly Impair Golgi Glycosylamentioning
confidence: 70%
“…It encodes a protein carrying a potential ATP/GTP binding motif that has numerous homologues in databases. The null mutant displayed slow growth and abnormal morphology (Lillo et al, 2000). Our data suggest that modifications in the wall of these cells may arise from impaired glycosylation.…”
Section: Deletions That Directly or Indirectly Impair Golgi Glycosylamentioning
confidence: 70%
“…Analyzing these genes, we found that 9 genes have been previously demonstrated to be essential ( YHR165C , YHR089C , YHR052W , YCR042C , YDR320C-A , YHR169W , YKL138C-A , YGL106W and YHR099W ) and other 14 genes ( YGR252W , YHR027C , YOL012C , YNL147W , YGL100W , YNL096C , YOL148C , YFL007W , YOL145C , YBR111W-A , YNL055C , YHR216W , YBL071W-A and YHR039C-A ) have been previously demonstrated to be non-essential by other investigators through small-scale gene deletion experiments in functional characterization studies [25-36] (Table 1). Among non-essential genes, 10 genes ( YGR252W , YHR027C , YOL012C , YNL147W , YNL096C , YOL148C , YOL145C , YBR111W-A , YNL055C and YHR039C-A ) have been shown to impair substantially the growth of S. cerevisiae when they are completely deleted [33,36-40], whereas the 4 remaining non-essential genes ( YGL100W , YFL007W , YHR216W and YBL071W-A ) have been shown not to affect the growth phenotype of yeast when they are deleted [34,35,41,42]. Although roughly 1/3 of the these genes predicted to be essential have been previously classified as non-essential, the complete deletions of most of them have been shown to severely reduce the fitness of organisms [33,36-40], suggesting that our predictor, even when directly contradicted by these experimental findings, can nonetheless identify genes important to cellular function.…”
Section: Resultsmentioning
confidence: 99%